BIOLOADS AND ENZYME ACTIVITIES OF PETROLEUM POLLUTED EFE RIVER WETLAND, UMULOLO, OKIGWE, IMO STATE. NIGERIA. - C. C., Ike, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The study investigated bioloads and enzyme activities of petroleum polluted Efe River wetland.The bioloads and trend of enzymatic activities in petroleum polluted and unpolluted wetlands wereevaluated using standard methods. Bioloads for all microbial groups enumerated, had highest valuesduring rainy season when compared with dry season counterpart. Total viable count (TVC) had highestcounts in the lightly polluted wetlands – rainy/ dry seasons {(3.9 ±0.19) x 105, (3.2 ±0.21) x 105},followed by control “unpolluted wetlands” {(3.4 ±0.17) x 105, (2.8 ±0.16) x 105} and lowest values inthe heavily polluted wetlands {(3.3 ±0.23) x 103, (2.8 ±0.29) x 103} respectively. The same trend wasobserved with other microbial groups assessed. Bacillus species was the most prevalent for bothseasons - lightly polluted wetlands – rainy/ dry season (87.5% ±0.11/ 75% ±0.16), heavily pollutedwetlands (50% ±0.32/ 25% ±0.15), and control “unpolluted wetlands” (75% ±0.14/ 62.5% ±0.24). Thevalues of soil enzymatic activities followed the same trend with bioloads. Dehydrogenase enzyme (µgTPF g-1 hr-1) activities recorded very high values (4658 ±57) in the assessed wetlands, unlike alkalinephosphatase enzyme that had the least values (82.67 ±1.12). High values of enzymatic activities wereobserved in lightly polluted wetland, followed by control (unpolluted wetland) and heavily pollutedwetland in that order. All values obtained in bioloads, prevalence and enzymatic activities, whencompared were statistically significant (p<0.05). This study has shown that petroleum on heavyimpaction could cause negative effects on wetlands bioloads and enzyme activities while lightimpaction encourages bioloads replication and increased enzyme activities resulting in improvedindicator values.